Peran Kepemimpinan, Disiplin, dan Motivasi Kerja dalam Meningkatkan Produktivitas Karyawan PT Nesia Pan Pacific - Melani Puspita Permata; Asnawi Hidayat (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of leadership style, work discipline, and work motivation on employee productivity at PT Nesia Pan Pacific Clothing Wonogiri. The research employs a quantitative approach using a survey method through questionnaires. The population in this study consists of all employees of PT Nesia Pan Pacific, with a sample of 98 respondents determined using the Slovin formula. Data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that both partially and simultaneously, leadership style, work discipline, and work motivation have a positive and significant effect on employee productivity. These findings affirm that efforts to improve employee productivity can be achieved through strengthening leadership roles, implementing consistent work discipline, and enhancing employee motivation. This study provides practical implications for company management in managing human resources more strategically and performance-oriented.